Assessment of total sialic acid levels in patients with hyperemesis gravidarum: a preliminary study. (19th May 2018) - Demir, Sevgi Sari; Özcan, Hüseyin Çağlayan; Balat, Özcan; Öztürk, Ebru; Uğur, Mete Gurol; Gündüz, Reyhan; Taysi, Seyithan
Abstract: To determine the levels of serum total sialic acid (TSA) in patients with hyperemesis gravidarum (HG) and their gestational age-matched controls. Thirty pregnant women with HG, and 30 healthy pregnant women at up to 14 weeks of gestation were enrolled in this preliminary study. Total sialic acid levels in maternal serum were measured using the quantitative sandwich ELISA method. We observed statistically significant difference in TSA levels between HG and the control groups ( p  = .003). The identification of the role of SA in the prediction, diagnosis and follow-up of HG warrants more comprehensive studies in the future. Impact Statement: What is already known on this subject? The derivatives of neuraminic acid are collectively referred to as sialic acid (SA). Changes in SA levels are known to trigger various conditions and disorders, including inflammatory, cardiovascular, neurological and endocrine diseases. Although a sensitive test capable of identifying hyperemesis gravidarum (HG) would be useful for diagnosis purposes, such a test is currently not available. Studies focussing on identifying new potential indicators and biomarkers for HG – as well as identifying their relevance in establishing diagnosis and assessing disease severity – would not only assist in elucidating the underlying causes of this condition but would also contribute to the development of new diagnostic tests for HG. What the results of this study add? Total sialic acid levels are significantly higher in sera of the patients with HG. The present study is the first in the literature to assess total sialic acid levels in patients with HG and healthy pregnant women before 14 weeks of gestation. What the implications are of these findings for clinical practice and/or further research? Total sialic acid levels could give an idea to clinicians in the etiopathogenesis of HG. The identification of the role of sialic acid in the prediction, diagnosis and follow-up of HG warrants more comprehensive studies in the future.